(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Teak species have been found to have effects on soil properties different from those of indigenous natural forests in terms of organic matter accumulation and soil properties on the forest floor. This research aims at evaluating the physico-chemical properties of soil under Teak plantations in Akanga Teak plantations, Nigeria. Soils were sampled and analyzed based on procedures described by Bouyoucos, Day, and Reeuwijk. Based on the results, soil particle size from the plantation had the highest percent of sand (74.5±1.1). There was a fluctuation of soil pH between the age series, 1981 age series had the highest pH (6.2±0.0) in both seasons. The nitrogen content had a steady declined as the plant age increased, while the organic matter and phosphorus content increased with the age of the plant species in the area. There was a decline in soil nutrients during the wet season, which also coincided with the active growth period of forest trees. Thus, it is evident from this study that monoculture plantation of exotic species may lead to an initial reduction of soil organic content and nutrient elements in the soil; then a gradual buildup of soil organic matter and exchangeable cations with age.